Flavonol glycosides and their α-glucosidase inhibitory effect from Camellia sinensis. (February 2020) - Cuc, Nguyen Thi; Anh, Luu The; Cuong, Nguyen The; Anh, Nguyen Hoang; Nhiem, Nguyen Xuan; Tai, Bui Huu; Hoai, Nguyen Thi; Yen, Pham Hai; Van Minh, Chau; Van Kiem, Phan
Graphical abstract: Highlights: Three new compounds were isolated from Camellia sinensis . The structures were successfully determined by spectroscopic evidence. Comp. 4 exhibited the strongest α -glucosidase inhibitory activity (57.2 %.). Comp. 1, 2, and 4 –8 showed α -glucosidase inhibitory activity with inhibitory percentages of 20.4–41.1 %. Abstract Two new flavonol glycosides, kaempferol 3- O - α -l -rhamnopyranosyl-(1→6)-[ α -l -arabinopyranosyl-(1→3)] [2-( Z )-coumaroyl]- β -d -glucopyranoside (1 ) and 4′ -O - α -l -rhamnopyranosylkaempferol 3- O - α -l -rhamnopyranosyl-(1→6)-[ α -l -arabinopyranosyl-(1→3)] [2-( Z )-coumaroyl]- β -d -glucopyranoside (2 ), one new megastigmane glycoside, (3 S, 9 R )-3, 9-dihydroxymegastigman-5-ene 9- O - β- d -apiofuranosyl-(1→6)- β- d -glucopyranoside (3 ), along with five known compounds, 7 S, 8 S - threo 4, 9, 9′-trihydroxy-3, 3′-dimethoxy-8- O -4′-neolignan 7- O - β -d -glucopyranoside (4 ), kaempferol 3- O - β -d -glucopyranoside (5 ), nicotiflorin (6 ), 4′- O - α -l -rhamnopyranosylnicotiflorin (7 ), and camelliquercetiside (8 ) were isolated from the methanol extract of the leaves of Camellia sinensis (L.) Kuntze. Their structures were elucidated by 1D, 2D NMR spectra, HR-ESI-MS, chemical methods, and by comparing with the NMR data reported in the literature. In addition, the α -glucosidase inhibitory activity of all compounds was evaluated. As the results, compound 4 exhibited the strongest α -glucosidase inhibitory activity (57.2 %), while flavonol glycosides 1, 2, and 5 -8 showed α -glucosidase inhibitory activity with inhibitory percentage ranging from 20.4 to 41.1 %.